Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Buosi, Gabriela G. P. [UNESP]; Neto, Arthur D. R. [UNESP]; Lopes, Paulo R. M. [UNESP]; Ferrari, Samuel [UNESP]; Guerreiro, Júlio C.; Filho, Pedro J. F.; Lima, Ronaldo C. [UNESP]; Nascimento, Vagner [UNESP]; Funichello, Marina; Raetano, Carlos G. [UNESP]; Prado, Evandro P. [UNESP] (Springer Nature, 2024)
The quantity and quality of spray deposition are fundamental for improving pesticide performance in plant pests. This study evaluated how spray droplet size (1) and spray nozzle type (2) affect the quantity and quality of spray deposition on peanut plants at the vegetative and reproductive growth stages. Two greenhouse experiments were performed on peanut plants at the V1 and R1 growth stages. Experiment 1 treatments included three droplet sizes: medium (flat fan XR 11002), very coarse (TT 11002), and extremely coarse (AIXR 11002). Experiment 2 treatments were five spray nozzles: hollow cone (TXA 8002 VK), twin flat fan (TTJ60 11002), air induction flat fan (AIXR 110025), drift guard twin flat fan (DGTJ60 11002), and extended range flat fan (XR 11003). Spray deposition values were determined using a solution of brilliant blue dye sprayed by a CO2-pressurized backpack sprayer. The medium droplet size provided higher spray deposition on peanut plants at the V1 and R1 growth stages. Increasing the droplet size from medium to extremely coarse reduces spray deposition at the V1 growth stage. Spray deposition uniformity increased as droplet size increased at the V1 growth stage. The spray uniformity decreased at the R1 growth stage as the droplet size increased. The flat fan XR 11003 (medium droplet) and hollow cone nozzle TXA 8002 VK (fine droplet) provided a higher spray deposition on peanut plants at both growth stages. The spray nozzles that provide a higher spray deposition did not perform well on spray uniformity.
Keywords: Application technology; Arachis hypogaea; Coverage; Spray drift; Spray retention